Identidad cultural y su relación con la vida comunitaria de los estudiantes de la UECIB 16 de noviembre, Guamote. - Caranqui Guambo, Lastenia Isabel (2024)
The present research, titled "Analysis of Cultural Identity and Its Influence on the Community Life of Students at UECIB November 16 in Guamote," addresses how the cultural identity of students influences their interactions and development within their community. The general objective is to examine the impact of cultural identity on the community life of students at the said institution. The methodology used in this study is qualitative, employing a non-experimental cross-sectional design. Surveys were conducted on students and interviews with teachers and parents to collect data on the perception of cultural identity and its manifestation in community life. The results reveal that the majority of students perceive that the teaching of local traditions is sufficient to understand their culture. Additionally, there is an observed preservation of local languages and dialects within the educational community. However, challenges are detected in integrating these cultural elements into the daily lives of students and in their participation in community activities. In conclusion, the research confirms that cultural identity plays a role in the development of students and their interaction with the community. It is proposed to strengthen the integration of cultural aspects into the educational curriculum and to promote the active participation of students in activities that reflect and celebrate their cultural identity.